The Effect of Capital Structure, Liquidity, and Profitability on Corporate Financial Performance - Purwasih, Rani; Suhardi; Makrus, Mohamad (Universitas Sulawesi Barat, 2025)
This study aims to determine the effect of capital structure, liquidity, and profitability on the financial performance of transportation and logistics sector companies listed on the Indonesia Stock Exchange during the 2020-2024 period. The variables used in this study include Debt to Equity Ratio (DER), Current Ratio (CR), and Return on Assets (ROA) as independent variables, and Return on Equity (ROE) as the dependent variable. The analysis method used is panel data regression with the Random Effect Model (REM) approach, which is analysed with Eviews 12 software. The results showed that capital structure (DER) has a negative and significant effect on financial performance (ROE), while liquidity (CR) and profitability (ROA) have no significant effect. However, simultaneously, the three variables have a significant impact on financial performance. This finding confirms the importance of optimal capital structure management in improving company performance, while liquidity and profitability require more effective strategies to contribute maximally to company profits.